The Influence of Product Quality, Nostalgia Perception, and Emotional Attachment on Repurchase Intention: Evidence from Bolu Rampah Consumers in South Sulawesi - Fika Kurniawaty; E. Elia Ardyan; Endi Sarwoko (STIE Amkop Makassar, 2026)
This study aims to analyze the influence of product quality, perceived nostalgia, and emotional connection on repurchase intention among consumers of the traditional culinary product The Bolu Rampah in South Sulawesi. The research is motivated by the shifting consumption patterns of society, particularly among younger generations, who tend to adopt modern foods and gradually abandon traditional culinary products. The Bolu Rampah, as a distinctive cake made from local spices, holds significant potential to be developed not only as a consumer product but also as a cultural identity symbol and regional specialty. This research employs a quantitative explanatory approach involving 150 respondents selected through purposive sampling, with the criteria of having purchased The Bolu Rampah at least once within the last six months. The research instrument was developed based on validated indicators from previous studies and measured using a five-point Likert scale. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that product quality, perceived nostalgia, and emotional connection have a positive and significant effect on repurchase intention. Among these variables, emotional connection is found to be the most dominant factor influencing repurchase intention. This finding suggests that consumer loyalty toward The Bolu Rampah is driven not only by functional product attributes such as taste and physical quality but also by emotional and cultural values embedded in the product. Practically, the findings highlight the importance of implementing emotional branding and cultural marketing strategies to strengthen The Bolu Rampah's identity as a signature souvenir of South Sulawesi that evokes not only sensory satisfaction but also collective memory and local pride.